Robust ultra-wideband tranceiver integrated circuit design - Batur, Okan Zafer. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Pulse-based wideband and UWB radios are well known for their use in radar technology. UWB has also been popular for its use on high data rate applications in recent years. UWB wireless sensor networks are known for their low power and long range operation. UWB is not only a low cost and low complexity technology with precise ranging and multipath immunity properties, but it also has certain challenges such as pulse based synchronization, which requires low jitter and precise delay blocks. In the dissertation, low-power, high data-rate, and moderate range IR-UWB transceivers are designed with robustness to impulsive noise. The non-idealities of the receiver and transmitted pulse are also studied to create an e cient IR-UWB transceiver. As a rst step, the existence of the impulsive noise in wideband channels is shown with measurements and tted noise models. Top level computer automated system models are written, extensive simulations are performed, and performance metrics are de ned. Then, these system models are converted to circuits in a top-down fashion. Various UWB transceiver architectures are reviewed in terms of performances and hardware complexity. Then, both coherent and non-coherent IR-UWB transceivers architectures are realized in standard CMOS technology. During the thesis work, three chips have been fabricated using UMC 130 MMRF technology. Co-planar waveguide FR4 PCBs and UWB antenna designs were realized to realize overall system and minimize coupling problems.
Keywords: Ultra-wideband devices.